Using Fruit Enzymes For Extraction And Characterisation Of Collagen From Black Tilapia (Oreochromis Niloticus) Skin - Zarini, An Nabil (2016)
Collagen is a type of fibrous protein that serves as structural protein in vertebrates. It serves as building blocks and provides flexibility for skin tissue, bone, cartilage and tendons. In most organisms, collagen relates to the muscle toughness. Collagens find it most valuable application in biomedical and pharmaceutical area as it serves as biological scaffolds. Collagens are widely used in industries as edible and photographic gelatin, sausage casings, leather industries, cosmetics and pharmacy. It also serves as supports for enzymes or biologically active compounds due to its special characteristics such as biodegradability and weak antigency properties (Lee et al., 2001).